(untitled) (Bioscience Journal, 2016)
The species Croton rhamnifolioides is a shrub popularly known as "quebra faca", utilized in teas or infusions for the treatment of gastrointestinal disorders as ulcers, gastric discomfort, vomiting and hemorrhagic diarrhea. This work has as its main objective to evaluate the chemical composition of the essential oil of the Croton rhamnifolioides leaves (EOC), antibacterial activity and modulatory activity of antibiotic resistance, against bacterial strains of Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa and, and antifungal activity against Candida albicans, Candida krusei and Candida tropicalis. The chemical composition was determined through chromatography with a gas phase coupled with mass spectrometry (CG/MS), whereas antimicrobial activity and modulation were determined by microdilution assay. The chemical composition of the oil revealed 21 compounds, with the major compounds being spathulenol (22.46%) and 1,8-cineol (18.32%). The antimicrobial activity was not significant with MIC>1024 Âµg/mL, however, was observed a synergistic interference when essential oil associated with the antibiotics aminoglycoside and Î²-lactam, and the antifungal polyene.